125k views
4 votes
-2/9 (-1/3 divied by 3/5)????????????????????????????? please hurry

User Null Head
by
5.7k points

1 Answer

4 votes

Answer:

2/405

Explanation:

Simplify the following:

(-2)/9×((-1)/3×1/3)/5

(-1)/3×1/3 = (-1)/(3×3):

(-2)/9×((-1)/(3×3))/5

(-1)/(3×3)×1/5 = (-1)/(3×3×5):

(-2)/9×(-1)/(3×3×5)

(-2)/9×(-1)/(3×3×5) = (-2 (-1))/(3×3×5×9):

(-2 (-1))/(3×3×5×9)

3×3 = 9:

(-2 (-1))/(9×5×9)

9×5 = 45:

(-2 (-1))/(45×9)

45×9 = 405:

(-2 (-1))/405

-2 (-1) = 2:

Answer: 2/405

User JAAD
by
6.4k points